Breaking and entering - Minghella, Anthony; Pollack, Sydney, 1934-2008; Law, Jude, 1972-; Binoche, Juliette, 1964-; Wright, Robin, 1966-; Miramax Films; Weinstein Company; Mirage Enterprises (Firm) ([S.l.] : Miramax Home Entertainment, 2006)
Will and Sandy are two architects working on a major urban renewal project in the King's Cross section of London. The area is unsafe and not ready for such a project and is best known as a place to pick up prostitutes or buy drugs. Will and Sandy move their offices into a nearby vacant warehouse. Will and his girlfriend Liv have to deal with her behaviorally challenged thirteen year old daughter. At the same time Will has to deal with constant burglaries at his new office. One night, he spots Miro trying to break into the building. He chases Miro to his run down apartment block and watches as he returns home to his mother, Amira. Soon, Will 'meets' Amira and they begin an affair. Amira quickly learns that Will holds the key to her son's future.
Bonus features: Feature commentary wiyh ditector Anthony Minghella -- Deleted Scenes with optional audio commentary by director Anthony Minghella -- Theatrical Trailer.
Originally released as a motion in 2006.
Director of photography, Benoit Delhomme ; edited by Lisa Gunning ; original score composed by Gabriel Yared & Underworld ; costumes designed by Natalie Ward ; production designer, Alex McDowell.
Jude Law, Juliette Binoche, Robin Wright Penn.
BBFO rating: 15 years and over; for strong language and moderate sex. IFCO rating: 18 years and over; for strong language and moderate sex.
English dubbed Italian, or German, or Turkish dialogue with optional English, Italian, German, Turkish, Arabic, Serbian, Croatian, Ukranian and Slovenian subtitles.
English subtitles for the hearing impaired.
Keywords: Adultery -- England -- London -- Drama; Robbery -- England -- London -- Drama; Refugees -- Bosnia -- Drama; Feature films; Fiction films